Neo-Nazi Violence and Ideology: Changing Attitudes toward Violence in Sweden’s Skinhead and Post-Skinhead Eras - Mattsson, Christer (Terrorism and political violence, 2023)
This study examines how ideology is narrated in the life stories of former and active Swedish neo-Nazis. Employing a social psychological and generational perspective toward the meaning-making process of the neo-Nazi ideology, this study investigates the role ideology plays in both former and active adherents’ narratives of engagement in the neo-Nazi movement. This study also analyzes the differences in how former and active neo-Nazis talk about violence and violent acts in the movement. In doing so, this study shows that there has been a decisive shift between activists from the skinhead era and post-skinhead era in respect to how they address and articulate ideological conviction and violence. Results also indicate that Sweden’s neo-Nazi movement has undergone an intellectualization process over the past few decades, with violence becoming increasingly politicized.